Evaluation of microneedling and 10% trichloroacetic acid peels Combination in the management of infraorbital dark circles in women (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The dark circles seen under the eyes are defined as homogeneous bilateral macular pigmented patches that extend below the lower eyelids. Dark circles are a skin problem with multiple causes, and the currently available treatment options include a number of topical brightening medications in addition to other options such as platelet-rich plasma injections, fillers, auto-fatgraphs, or treatment with different types of lasers. Therefore this study was conducted to evaluate the efficiency microneedling and 10% trichloroacetic acid peels Combination in the  management of infraorbital dark circles in women.Materials and Methods: The study included 30 patients, their ages ranged between 20 and 48 years. Each of them underwent four treatment sessions two weeks apart, where the Dermapen device was applied to the dark circles area, then 10% chlorine-acetic acid was applied for five minutes, then it was modified using distilled water.Results: The study showed the effectiveness of the treatment, most of the patients showed an improvement over the treatment, where the improvement rate reached 90% of the study patients. The treatment sessions were well tolerated by the patients and the treatment was safe as no permanent side effects were recorded and some cases of erythema and Edema, both of which regress spontaneously within less than 24 hours.Conclusions: Our study showed that the combined microneedling treatment with 10% trichloroacetic acid is a safe and effective treatment with no significant side effects and can be considered as a low-cost therapeutic alternative compared to other treatment options.